2010
DOI: 10.1111/j.1365-2966.2010.16608.x
|View full text |Cite
|
Sign up to set email alerts
|

The Parkes Galactic Meridian Survey: observations and CMB polarization foreground analysis

Abstract: We present observations and cosmic microwave background (CMB) foreground analysis of the Parkes Galactic Meridian Survey, an investigation of the Galactic latitude behaviour of the polarized synchrotron emission at 2.3 GHz with the Parkes Radio Telescope. The survey consists of a 5 • wide strip along the Galactic meridian l = 254 • extending from the Galactic plane to the South Galactic pole. We identify three zones distinguished by polarized emission properties: the disc, the halo and a transition region conn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…No significant power is found in any other case. The non-detection of foreground power at > 75 is consistent with the expected foreground dependence: ∝ −2.5 (Carretti et al 2010), and the low power found inĈ KK b=1 . The excess power observed in the first EE bin of CMB-1 is fully consistent with a typical synchrotron frequency spectrum.…”
Section: Foreground Analysissupporting
confidence: 66%
“…No significant power is found in any other case. The non-detection of foreground power at > 75 is consistent with the expected foreground dependence: ∝ −2.5 (Carretti et al 2010), and the low power found inĈ KK b=1 . The excess power observed in the first EE bin of CMB-1 is fully consistent with a typical synchrotron frequency spectrum.…”
Section: Foreground Analysissupporting
confidence: 66%
“…The power decreases as a power law from the smallest sampled multipole to ∼ 10 3 . If we consider the trend in this portion of the plot as a simple power law of the form P( ) ∝ −α , the index α is usually reported in similar studies e.g., Haverkorn et al (2003), Giardino et al (2002), Carretti et al (2010). Other structures in the power spectra are not universally seen, though Haverkorn et al (2003) and Carretti et al (2010) do mention a flattening at high multipoles due to noise in the image.…”
Section: Calculating Angular Power Spectramentioning
confidence: 83%
“…In this paper we take a third approach, using statistical methods to examine the spatial scales of polarization structures. Such analysis has been done before with focus on calculating the angular power spectra or the structure functions of the polarized emission (Tucci et al 2000;Giardino et al 2001;Tucci et al 2002;Bruscoli et al 2002;Giardino et al 2002;Haverkorn et al 2003Haverkorn et al , 2004Haverkorn et al , 2006Haverkorn et al , 2008La Porta & Burigana 2006;Carretti et al 2005Carretti et al , 2010 . More recently, the work of Gaensler et al (2011) demonstrated that the statistics of the gradient of polarized emission provided clear measurements of the magnetoionic medium.…”
mentioning
confidence: 99%
“…S-PASS is a single-dish polarimetric survey of the entire southern sky at 2.3 GHz, performed with the Parkes 64 m Radio Telescope and its S-band receiver with beam width FWHM=8.9 arcmin (Carretti et al, in prep. and Carretti et al (2013), see also Carretti et al (2010) and Iacobelli et al (2014)). Final maps were convolved with a Gaussian window of FWHM = 6 arcmin to a final resolution of 10.75 arcmin.…”
Section: Observationsmentioning
confidence: 85%
“…As noticed by Robitaille & Scaife (2015), the wavelet power spectra do not sample properly the drop of power caused by the telescope beam. Thus, in order to measure power laws corrected for the effective beam, Fourier power spectra have been fitted with a similar relation to that of Carretti et al (2010) :…”
Section: H II Regions Snrs and Small-scale Featuresmentioning
confidence: 99%